2013
DOI: 10.1002/ejsp.1995
|View full text |Cite
|
Sign up to set email alerts
|

The effects of counterfactual defences on social judgements

Abstract: Research on counterfactuals (‘If only…’) has seldom considered the effects of counterfactual communication, especially in a defensive context. In three studies, we investigated the effects of counterfactual defences employed by politicians. We assumed that self‐focused upward counterfactuals (‘If only I…, the outcome would have been better’) are a form of concession, other‐focused upward counterfactuals (‘If only they…, the outcome would have been better’) are a form of excuse, and self‐focused downward counte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 72 publications
4
21
0
Order By: Relevance
“…After a negative life event, people often imagine the good things that could have happened to them if not for other people's actions. Other-referent upward counterfactual thinking is a cognitive activity that pertains to envisioning how negative life events could have been better and how other people were responsible for such undesired outcomes (Callander, Brown, Tata, & Regan, 2007;Rye, Cahoon, Ali, & Daftary, 2008) (or "other-focussed"; Catellani & Bertolotti, 2014;Roese & Epstude, 2017). For example, after not having achieved an important goal, one may think: "If only my colleague was more responsible, then this project would've been successful.".…”
Section: Introductionmentioning
confidence: 99%
“…After a negative life event, people often imagine the good things that could have happened to them if not for other people's actions. Other-referent upward counterfactual thinking is a cognitive activity that pertains to envisioning how negative life events could have been better and how other people were responsible for such undesired outcomes (Callander, Brown, Tata, & Regan, 2007;Rye, Cahoon, Ali, & Daftary, 2008) (or "other-focussed"; Catellani & Bertolotti, 2014;Roese & Epstude, 2017). For example, after not having achieved an important goal, one may think: "If only my colleague was more responsible, then this project would've been successful.".…”
Section: Introductionmentioning
confidence: 99%
“…Our findings therefore contribute to extending this area of research from the intra- In our research, counterfactuals were produced by an allegedly neutral and authoritative source, namely an expert witness. Past research carried out in the political field has found that the influence of counterfactual communication can diminish or even disappear when the counterfactual source is perceived as unreliable (Catellani & Bertolotti, 2014b). This might be the case also in the judicial field.…”
Section: Discussionmentioning
confidence: 95%
“…As mentioned in the introduction, according to previous research the focus of counterfactuals often affects not only causal explanation but also responsibility attribution, with individuals being more likely to attribute responsibility for the outcome to the actor on whom the counterfactual thought is focused on (Catellani & Bertolotti, 2014a; Nario‐Redmond & Branscombe, 1996). We expected that this would be the case also when lay jurors and judges are exposed to counterfactuals embedded in an expert witness' report.…”
Section: Research Overview and Hypothesesmentioning
confidence: 98%
See 2 more Smart Citations